Feasibility study of TiO[2] intermediate coating layer for adhesive strength improvement / Muhammad Firdaus Othman - Muhammad Firdaus , Othman (2013)
The effects of intermediate TiO2 coating layer on the adhesion strength improvement of TiN coating were studied. Ti/TiO2/TiN coatings were deposited by D.C magnetron sputtering on high speed steel (HSS) and stainless steel (SS) substrates. A series of dense and uniform coating films, 844.1 – 926.4 nm thickness, were deposited at discharge power of 150 W and substrate temperature ranging from 50 to 250 °C. The duration time for depositing Ti coating layer was 2400 s and for TiN and TiO2 coating layer were 3600 s each. The as-deposited coating films were heat treated (annealed) for 1 hour at 400, 500 and 600 °C. The adhesion strength of Ti/TiO2/TiN coatings were evaluated by scratch testing and the coating hardness values were measured using micro-hardness tester. X-ray diffraction (XRD) analysis revealed anatase TiO2 phase. The results from the scratch test discovered that Ti/TiO2/TiN coating exhibits higher adhesion strength compared to Ti/TiN and single layer TiN coating. The maximum adhesion strength of 1417.19 mN was observed for Ti/TiO2/TiN coating deposited on HSS substrate. It is also observed that Ti/TiO2/TiN coatings deposited at higher deposition temperature exhibits higher values of critical load. The adhesion strength of Ti/TiO2/TiN coating also increases as the TiO2 coating thickness increases. The adhesion strength of Ti/TiO2/TiN coating deposited on HSS decreases with the increases of substrate surface roughness. It was also observed that annealing Ti/TiO2/TiN coating at 500 °C yielded highest adhesion strength and coating hardness. The annealed coating at 600 °C revealed film delamination and exhibited lowest adhesion strength.